DAMPAK KESALAHAN BERBAHASA INDONESIA DALAM LAPORAN AKUNTANSI TERHADAP PEMAHAMAN PENGGUNA LAPORAN KEUANGAN - Fania Afrillia; Hafiz Hasibuan; Laura Jessica Napitupulu; Sri Muliani; Susi Bayu Br Batunanggar; Ayu Nadira Wulandari (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2025)
This research aims to analyze the impact of Indonesian language errors in accounting reports on users' understanding of financial reports. Language errors, both in terms of grammar and use of terms, can affect the quality of understanding of the information conveyed in accounting reports. The sample for this research consisted of 50 students majoring in accounting at Medan State University (UNIMED). The method used is a qualitative approach with data collection techniques through questionnaires, where respondents are asked to provide responses to a number of statements related to the influence of language errors in accounting reports. This data collection focuses on aspects of errors in the use of accounting terms, grammar, clarity of sentences, and the influence of writing errors on the trustworthiness of information. Based on a survey involving 50 accounting students, the results showed that language errors, such as the use of inappropriate terms and ambiguous sentences, greatly impacted their understanding of the financial information presented. The majority of respondents (86.3%) agreed that they often encounter language errors in accounting reports and are a disturbing factor in the process of understanding financial data.